Error Analysis on Passive Sentences Construction Made by the Eleventh Year Students of MA Assulaimaniyah Mojoagung - Ana Ainurrohmah; Adi Yusuf; Binti Qani’ah; Wim Banu Ukhrowi (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2022)
This research analyzed on passive sentences construction in the form of present and past tense. It focused on what types of passive sentences error made by  students and how do the students made errors. The aims of this research were to describe the types of passive sentences error and how the students made the errors. Qualitative research was the method of this research. The participants of this  research were the eleventh grade students of MIA at MA Assulaimaniyah Mojoagung consisting of 18 students. The data  of this research was the sentences of passive voice containing errors made by students. The findings showed that there were four types of error identified in passive sentences construction made by students: omission, addition, misfomation, and misordering. Most of students got difficulties in differentiating between regular and irregular verb in passive sentence construction. It can be concluded that the students are still lack of understanding of verb usage in passive sentence construction.